Positive and negative role of negative ions in cosmic exploration - Gretchikhin, Leonid I. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: At altitudes of 80 to 40 km, while the spacecraft made of duralumin without a thermal-protective coating was descending from the flight orbit at the first and second cosmic velocities, data were obtained on the increase in density, pressure, and temperature behind the shock front, as well as on the backout of the shock wave from the surface of the descending spacecraft.Methods: Calculations were made of the energy fluxes on the surface of the spacecraft for every 10 km, for convective and radiative heat transfer, as well as for the impact of electrons produced due to ionization of negative ions.Results: At the first cosmic velocity, the greatest energy flux is realized under the influence of an electron flux, and at the second cosmic velocity, radiative heat transfer occurs. In the shock-compressed gas at all the considered altitudes, pressure increases instantly to a value of 109 ÷ 1011 Pa, which leads to a sequential explosion with increasing power resulting in shock waves in the surrounding atmosphere and compression waves in the entire aircraft structure. The last most powerful explosion occurs at an altitude of approx. 40 km.Conclusion: The descending aircraft is destroyed into separate small parts to the size of small dust particles.
Keywords: negative ions; spacecraft; charging; convective heat transfer; radiative heat transfer; ionization phenomenon; shock waves; explosion